Ultrasensitive MRI detection of spontaneous pancreatic tumors with nanocage-based targeted contrast agent. (January 2018) - Kawano, Takahito; Murata, Masaharu; Kang, Jeong-Hun; Piao, Jing Shu; Narahara, Sayoko; Hyodo, Fuminori; Hamano, Nobuhito; Guo, Jie; Oguri, Susumu; Ohuchida, Kenoki; Hashizume, Makoto
Abstract: Contrast agents with greater specificity and sensitivity are required for the diagnosis of pancreatic cancers by magnetic resonance imaging (MRI). In this study, small heat shock protein 16.5 (Hsp16.5)-based nanocages conjugated to gadolinium(III)-chelated contrast agents and iRGD peptides (which target neuropilin-1 expressed on pancreatic cancer cells) were developed. To investigate whether template size influences relaxivity, nanocages with one to four hydrophobic domains were designed. MRI data showed that larger nanocages had higher T 1 relaxivity than smaller nanocages, which resulted from a reduction in molecular tumbling rates caused by an increase in nanocage size, and a robust cage structure resulting from the introduction of hydrophobic domains. For in vivo MRI studies, the engineered nanocages were evaluated using the Kras G12D ; Trp53 R172H ; Pdx-1Cre (KPC) transgenic mouse models, which develop clinically relevant pancreatic tumor under normal processes of angiogenesis, immune function and inflammation. Molecular MRI with protein nanocages was enabled to detect neuropilin-1-positive cells and to produce strong signal enhancement of spontaneous pancreatic tumors in KPC genetically engineered mouse models. Novel iRGD-modified nanocages displayed potential as a specific and sensitive MRI contrast agent for the diagnosis of pancreatic tumors for clinical translation. Graphical abstract: